Sustainable Financing and Enhancing the Role of Islamic Banks in Malaysia - Kunhibava, Sherin; Ling, Sarah Tan Yen; Ruslan, Md Khalil (Brill Academic Publishers, 2018)
Although the banking sector does not directly affect the environment, it can pursue environmentally friendly practices and reduce waste. Moreover, it can promote environmentally sustainable investments and encourage businesses to adopt similar practices. Because Islam encourages preservation and prohibits harm to the earth, Islamic banks are expected to follow such practices in pursuit of Sharīah compliance. In Malaysia, Islamic banks have already embarked on this path, mainly by practising conservation in operational matters; however, other areas of sustainable financing have been less enthusiastically pursued. This study recommends a three-level approach: (1) at the banking level, more proactive steps should be taken, e.g. greening operations, introducing environmentally friendly products and services, complying with environmental regulations, creating awareness and training stakeholders; (2) at the national level, the Central Bank should introduce appropriate policies and guidelines; and (3) at an international level, voluntary principles should be adopted to ensure compliance with global initiatives.